Benjamin Stanford: capstone - Stanford, Benjamin, artist (Colorado State University. Libraries, 2016)
The artist's statement: Throughout the course of my academic training, I have always found myself drawn to the human figure. While I continually push myself to explore new ways of approaching the figure, I find the aspects of tradition and craftsmanship to be a place where I feel at home and comfortable in the creative process. While capturing the likeness of my subject is of high priority, I try to strike a balance between deliberate rendering of form and intuitive response; providing a space where formal considerations interweave with the beauty of the human figure, culminating to something that is more than just a portrait. The human presence is something that is not solely encapsulated by physicality, but is a landscape that forms around emotions, values, and spirit. I strive to excavate these qualities and bring them to the surface. Rarely, if ever, are we allowed opportunities to have an unbroken extended gaze at another person. My art is an invitation to have that experience. In many ways, painting becomes less about simply portraying what I see, and aligns more with the process of translation. This notion of translation not only allows me room to set up a corresponding dialogue through the use of color and atmosphere, but provides a space where the portrait not only reflects the sitter, but inevitably becomes a portrait of the artist as well.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting